In the eye of the storm: An analysis of internal conflict in South Sudan's Jonglei State (Tufts Archival Research Center, 2018)
In the eye of the storm: An analysis of internal conflict in South Sudan's Jonglei State. Working Paper 11, by Rachel Gordon